IbM PENGEMBANGAN DESAIN PRODUK KERAJINAN BERBAHAN LIMBAH KAYU DI KLATEN - Tri Prasetya Utama; I Nyoman Suyasa (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2019)
Community service activities aim to develop the ability of craftsmen in improving the quality and quantity of products. improving the competitiveness of partners in facing the global market. The intended development includes; design, HRM, tools, management, strategy and marketing materials. Partners of this devotion activity is Haryono Wood Craft in Serenan, Kalten and Luphy craft located in Pedan Klaten, Central Java Province. The prospect of product development of wood-based wasted fabrics is very good and in demand by consumers widely. The limited ability of human resources, business networks, and the limited equipment and dependence of the finishing process on the weather cause the partners are less able to take advantage of opportunities to develop this business with the maximum. After accompaniment, the partners are expected to be able to become more powerful craftsmen, so as to increase the production, design quality, to increase the selling value of the product, so as to increase the family’s income, then more to absorb the labor that comes from the surrounding community. Community service activities are carried out during the period of one year. The planned activities are; workshop on the use of production tools with appropriate technology, management training, marketing-making workshop, and product development design workshops that are in demand by the market. After getting a good touch of design, proper management, modernization of production tools, attractive promotional media is expected to increase the competitiveness of partners in the face of the market.